The effectiveness of a project based program in developing English speaking skills among intermediate school student in Kuwaiti schools - Eman Manee Mohamed; Awatef Ali Shair; Hasaan hasan Khalifa (2024)
This study aimed at examining the effectiveness of a proposed program based on project based instruction in developing English speaking skills among intermediate stage students in Kuwait schools. Divided into two groups, the participants in this study comprised fifty third year intermediate Kuwaiti students, who were randomly selected from the public intermediate students in Kuwait in the school year 2022-2023. The study employed a quasi-experimental design in which two groups were assigned an experimental group (n=25) and a control one (n=25). The researcher taught the experimental group, who studied the proposed program, and the control group, who studied the regular program. Instruments of the study were composed of a speaking skills checklist, a scoring rubric, and a pre-post speaking test. The results of the study indicated that the experimental group students scored significantly higher than those of the control group on the speaking test, proving that there is an outperformance of the experimental students in speaking skills. Consequently, project- based instruction is an effective method to teaching speaking skills for third year intermediate Kuwaiti students if properly implemented.
(3CUHMJ GddZI GdGfLdjRjI dZI dgG OhkQG eMhQkjG aj GdeLJeY GdYGdej hJYJHQ egGQGJ GdJMOK ef Cge GdegGQGJ GdCSGSjI GdJj jfHZj JWhjQgG dJTLjY gDdGA GdWdGH ddeTGQcI aj eMGOKI aYGdI aLGA gPG GdHMK cHMK THg JLQjHj dJLQHI CKQ JONd GdeTQhY aj JOQjS egGQGJ GdJMOK ddGQJbGA HgG(B.s
Thesis (Ph.D)-Cairo University, 2024.
Bibliography: pages 92-99.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: English language; Project-based Instruction -- English Speaking Skills -- Kuwait Schools -- Intermediate Stage